2011
DOI: 10.1016/j.phytochem.2011.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive saponins from Microsechium helleri and Sicyos bulbosus

Abstract: Eleven oleanane-type saponins (1-11) have been isolated from Microsechium helleri and Sicyos bulbosus roots and were evaluated for their antifeedant, nematicidal and phytotoxic activities. Saponins {3-O-β-D-glucopyranosyl (1→3)-β-D-glucopyranosyl-2β,3β,16α,23-tetrahydroxyolean-12-en-28-oic acid 28-O-α-L-rhamnopyranosyl-(1→3)-β-D-xylopyranosyl-(1→4)-[β-D-xylopyranosyl-(1→3)]-α-L-rhamnopyranosyl-(1→2)-α-L-arabinopyranoside} (1), and {3-O-β-D-glucopyranosyl-2β,3β,16α,23-tetrahydroxyolean-12-en-28-oic acid 28-O-α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…These kinds of compounds have also been reported to have detrimental effects on plant growth when released into the soil . These compounds have recently been investigated for their phytotoxic activity . As a result, a long glycosidic chain linked at C‐3 of the aglycone moiety was suggested as a key factor for phytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of compounds have also been reported to have detrimental effects on plant growth when released into the soil . These compounds have recently been investigated for their phytotoxic activity . As a result, a long glycosidic chain linked at C‐3 of the aglycone moiety was suggested as a key factor for phytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…49 -51 These compounds have recently been investigated for their phytotoxic activity. 52 As a result, a long glycosidic chain linked at C-3 of the aglycone moiety was suggested as a key factor for phytotoxicity. In contrast, the relationship between aglycone structure and phytotoxicity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these compounds acted as postingestive antifeedants with varying potencies (3 > 12 > 14) with 12 having additional toxic action. The structure-activity relationships (SAR, Table 2) of these compounds showed that the most active IGRs (insect growth regulators) had a C-3 carbonyl group and a C-8 epoxide (7,12,18).…”
mentioning
confidence: 99%
“…469 In the same way, saponins from Microsechium helleri and Sicyos bulbosus showed significant postingestive effects on Spodoptera littoralis larvae. 470 The search for limonoids started way back when scientists started looking for the factor responsible for bitterness in citrus which has a negative impact on citrus fruit and the juice industry worldwide. The term limonoids was derived from limonin, the first tetranortriterpenoid obtained from citrus bitter principles.…”
Section: Triterpenesmentioning
confidence: 99%